Common Sense - Greenwald, Ted (Wesleyan poetry., 2016)
First published in 1979, Common Sense evinces a spare street-wise style rooted in the vernacular of the city. Now something of a cult classic, the book is recognized as an understated masterpiece, pushing at the edges of spoken word. This is the language of everyday, brought onto the page in such a way that we never lose the flow of speech and at the same time we become attuned to its many registers--musical, emotional, ironic. Ted Greenwald's work has been associated with several major veins of American poetry, including the Language movement and the New York School, but it remains unclassifiable. An online reader's companion will be available at $utedgreenwald.site.wesleyan.edu.